VALIDITY AND EFFECTIVENESS OF PHYSICS LEARNING PACKAGE BASED ON GUIDED-INQUIRY MODEL - Aliffianto, Agung (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
The aim of this research is to know the validity and effectiveness of physics learning package based on Guided Inquiry. This research uses development method with Plomp and Nieven research design. Physics learning package that have been developed and then validated by three expert validators from UNESA. Validated sections include Syllabus, RPP Scenario, Student Book, and Student Worksheet.The result of validated, the first is Syllabus that has a high validity with 3.79 average score. Second, the validity score of RPP Scenario is 3.71 with high valid category. Third, the Student Book has a validity score of 3.47 with valid category. Last, Student Worksheet has validity of 3.71 with high validity category. The result of effectiveness can be seen before and after using learning instrument that developed. Before using the developed learning instrument, the student's Science Process Skills score averaged 29.2, while after using the developed instrument, the student's Science Process Skills score was 85.7. Based on the results of the validity and effectiveness of the instrument shows that the instructional instrument of physics based on Guided Inquiry is very suitable to be used in learning to improve student?s Science Process Skills